Reviewing risks and vulnerabilities in web 2.0 for matching security considerations in web 3.0 - Saqib, Nazar Abbas; Salam, Asiya Abdus; Atta-Ur-Rahman; Dash, Sujata (Journal of discrete mathematical sciences & cryptography, 2021)
Web 2.0 has entirely revolutionized the web and the ways people use it by bringing enhancements in information discovery, retrieval, and aggregation. It has also brought improvements in various aspects like content controlling, content structuring, web technologies, applications, communication, marketing and selling. On the one hand, these improvements are providing extensive benefits while, on the other hand they are compromising fundamental requirements of security and confidentiality. The vulnerabilities and security risk associated with these enhancements are becoming a major security threats to the organizations and laymen. In this paper, we have discussed the features and improvements brought in web 2.0 and the security risks associated with them which will set a road map towards the necessity of web 3.0.